Preparation of high-strength TC4/304 dissimilar joint with TA2/304 composite interlayer by a dual-pass laser. (October 2022) - Zhang, Yan; Gao, YiDi; Yu, DeShui; Zhou, JianPing; Sun, DaQian
Highlights: A composite joint based on two different joining mechanisms. The unmelted composite interlayer prevented the formation of brittle Ti-Fe intermetallics in the joint. The unmelted composite interlayer was beneficial to relieve and accommodate the thermal stress. Abstract: Joining titanium (Ti) alloy to stainless steel (SS) is of great interest for applications in the marine and aerospace fields. Despite the importance, no joining techniques have been developed that avoid the formation of brittle intermetallic compounds (IMCs) to produce high strength joints. In this work, TA2/304 explosive welding composite plates was used as an interlayer to prevent the formation of these brittle phases when joining TC4 to 304 SS. The presence of this TA2/304 composite interlayer (CI) was performed ensured that crack free welds were obtained and no brittle IMCs were observed. The TA2/304 CI was produced by explosive welding, the length of explosive welding interface (EWI) in TA2/304 CI raged 1–10 mm. In addition, TA2 and 304 was remained in CI as enlarged ends to weld with TC4 and 304 base materials by laser welding, respectively. TA2/304 CI did not melt during the joining process, acting as a barrier between the TC4 and 304 base materials. Mechanical testing of the joints revealed that the strength of the TC4/304 joint increased with the increasing of EWI in TA2/304 CI. The tensile strength of joint could reach 545 MPa and the fracture at TA2 side of CI when the length of EWI was above 8 mm.